Cortico-muscular coupling and motor performance are modulated by 20 Hz transcranial alternating current stimulation (tACS) in Parkinson’s disease - Krause, Vanessa; Wach, Claudia; Suedmeyer, Martin; Ferrea, Stefano; Schnitzler, Alfons; Pollok, Bettina (Frontiers in Human Neuroscience, 2014)
Parkinson’s disease (PD) is associated with pathologically altered oscillatory activity. While synchronized oscillations between 13 and 30 Hz are increased within a cortico-subcortical network, cortico-muscular coupling is decreased. The present study aims at investigating the effect of non-invasive transcranial alternating current stimulation (tACS) of the primary motor cortex (M1) on motor symptoms and motor-cortical oscillations in PD. In 10 PD patients and 10 healthy control subjects, static isometric contraction, dynamic fast finger tapping and diadochokinesia of the more severely affected hand were investigated prior to and shortly after tACS of the contralateral M1 at 10 Hz vs. 20 Hz vs. sham. During isometric contraction, neuromagnetic activity was recorded using magnetoencephalography. 20 Hz tACS attenuated beta band cortico-muscular coupling during isometric contraction and amplitude variability during finger tapping in PD patients but not in healthy control subjects. 10 Hz tACS yielded no significant after-effects. The present data suggest that PD is associated with pathophysiological alterations which abet a higher responsiveness towards frequency-specific tACS – possibly due to pathologically altered motor-cortical oscillatory synchronization at frequencies between 13 and 30 Hz.